2021
DOI: 10.1096/fj.202002346rr
|View full text |Cite
|
Sign up to set email alerts
|

Associations of essential and toxic metals/metalloids in whole blood with both disease severity and mortality in patients with COVID‐19

Abstract: The variations and dynamics of essential and toxic metal(loid)s in patients with COVID-19 may associate with the progression and fatal outcome of the disease, which still remains to investigate. In the present study, a retrospective analysis was performed in a cohort of 306 confirmed COVID-19 patients admitted to Tongji hospital (Wuhan, China) from February 10 to March 15, 2020. Whole blood levels of essential and/or toxic metal(loid)s were analyzed, including magnesium, calcium, chromium, manganese, iron, cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 50 publications
9
67
1
9
Order By: Relevance
“…However, the difference in blood Cu concentration in relation to severity of COVID-19 was small, i.e., in the range of 10% only, and again not compatible with a vivid and strong positive acute phase response to the infection. This notion is supported by a relatively unchanged Cu status in COVID-19 during the hospital stay, as observed both in the analysis of full blood in the study from Wuhan [60], and in our present analysis of serum Cu and CP in German patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the difference in blood Cu concentration in relation to severity of COVID-19 was small, i.e., in the range of 10% only, and again not compatible with a vivid and strong positive acute phase response to the infection. This notion is supported by a relatively unchanged Cu status in COVID-19 during the hospital stay, as observed both in the analysis of full blood in the study from Wuhan [60], and in our present analysis of serum Cu and CP in German patients.…”
Section: Discussionsupporting
confidence: 87%
“…Whether these dynamics constitute a positive and pregnancy-supporting response is unknown at present. A very recent analysis of full blood trace elements in COVID-19 from Wuhan, China, indicated a generally increased Cu status in the more severely diseased patients, without observing a difference in full blood Cu when comparing survivors and nonsurvivors [60]. However, the difference in blood Cu concentration in relation to severity of COVID-19 was small, i.e., in the range of 10% only, and again not compatible with a vivid and strong positive acute phase response to the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the balance of mineral status in body fluids and exhaled breath of COVID-19 patients might be significantly influenced through a yet-to-be-discovered bioinorganic mechanism. Zeng et al [ 26 , 28 ] applied ICP-MS to determinate various elements, including Mn, Ca, Cr, Mn, Fe, Cu, Zn, As, Cd, Hg, Tl, Pb, and others from COVID-19 and non-severe COVID-19 patients’ body fluids. These studies revealed that significant variations of elements associated with the disease development of COVID-19 can be performed using ICP-MS.…”
Section: Ms-based Multidimensional Breath Analysismentioning
confidence: 99%
“…Zeng et al [ 77 ] analyzed over 300 patients and found that severe cases (defined as those having oxygen saturation ≤ 93% at rest, or PaO 2 /FiO 2 ≤ 300 mmHg, or requiring ICU care) showed significant lower levels of magnesium than mild and moderate cases, though all values remained within the reference range. Such difference was found consistently over the clinical course since disease onset.…”
Section: Introductionmentioning
confidence: 99%